Answer:
y = -2x +20
6x - 5y = 12
Put the value of y in 2nd equation
6x - 5( -2x +20 ) = 12
6x +10x -40 = 12
16x = 12 +40
16x = 52
x = 13/4
Putting the value of x in equation 1
y = -2x +20
y = -2(13/4 ) +20
y = 27/2
Do mark me as brainly. THANKS
Answer:
x=3
Step-by-step explanation:
The transformation of <span>f(x)=15tanx would be achieved by dilating y</span>=tanx graph 15 times. This transformation will cause y'=15 y. This will increase the value of dilation become 15 times of the original
The transformation of g(x)=15tanx would be achieved by shifting y=tanx graph 15 right. This transformation will cause x'=x+15. This will change the value from tan x into tan(x+15)
The answer is -8 I know this as well as
Answer:
Step-by-step explanation:
(3m-1)(6-a)-(m+3)(6-a)
=3m(6-a)-1(6-a)-m(6-a)+3(6-a)
=18m-3ma-6+a-6m+ma+18-3a
=12m-2ma+12-2a
=2(6m-ma+6-a)